The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s13640-019-0483-y
|View full text |Cite
|
Sign up to set email alerts
|

Regularized super-resolution restoration algorithm for single medical image based on fuzzy similarity fusion

Abstract: Medical images are blurred and noised due to various reasons in the acquirement, transmission and storage. In order to improve the restoration quality of medical images, a regular super-resolution restoration algorithm based on fuzzy similarity fusion is proposed. Based on maintained similarity in multiple scales, the fused similarity of the medical images is computed by fuzzy similarity fusion. First, fuzzy similarity is determined by the regional features. The images with certain similarity are obtained acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Several studies reported positive impacts of SR models on medical interpretation and diagnosis [2,5,6]. Specifically, it has been reported [5] that constructing HR images via SR models allows detection and recognition of subtle lesions, and reduce the misdiagnosis rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported positive impacts of SR models on medical interpretation and diagnosis [2,5,6]. Specifically, it has been reported [5] that constructing HR images via SR models allows detection and recognition of subtle lesions, and reduce the misdiagnosis rates.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported positive impacts of SR models on medical interpretation and diagnosis [2,5,6]. Specifically, it has been reported [5] that constructing HR images via SR models allows detection and recognition of subtle lesions, and reduce the misdiagnosis rates. In addition, it has been reported [2] that enhancing image resolution can often improve the performance of several subsequent tasks including detection, segmentation, and classification.…”
Section: Introductionmentioning
confidence: 99%